Perbedaan Konflik Kerja Generasi Baby boomers dan Millenial Pada Karyawan PT. Pelindo Persero Regional 1 Cabang Belawan - Hasan, Ahmad Mu’arif; Dewi, Salamiah Sari (Jouska: Jurnal Ilmiah Psikologi, 2024)
This study aims to compare work conflicts between baby boomers and millennial employees at PT. Pelindo Persero Regional 1 Belawan Branch. Work conflict is a mismatch between individuals in the company that involves differences in opinions, values, goals, and competition for positions and power in achieving organizational goals. This research method is quantitative with all employees of PT. Pelindo Persero Regional 1 Belawan Branch (60 people) as population and sample. The sampling technique uses total sampling. Data collection using Work Conflict Scale with Likert scale model. Data analysis was performed with Anova test and reliability using Cronbach alpha coefficient. The results of the analysis showed the significance of the coefficient of difference in work conflict of 329.874 (p 0.05), which indicates a high level of work conflict in both generations. Thus, the hypothesis was accepted, suggesting the existence of differences in labor conflicts between the two generations.